An Evaluation of Nutritional Security Impacts of Climate-Smart Adaptation Practices among Smallholder Farmers of Eastern Oromia, Ethiopia - Beyan Ahmed Yuya; Jema Haji Mohammed; Mengistu Ketema Aredo (Turkish Journal of Agriculture: Food Science and Technology, 2022)
Climate impact mitigation through improved agricultural practices is one means by which agricultural productivity increases to meet the growing food demands in the world. This study evaluated the impacts of climate-smart Practices on rural households’ nutrition security. The study used both primary and secondary data sources. Primary data was collected from sample respondents in the 2020/21 production year. Descriptive statistics and econometric models were employed for data analysis. Multinomial logit result indicated that the probability of adopting climate-smart agricultural practices is influenced by the education level of the head, extension contact, livestock holding, membership coop, market information, advice on land management, climate change information, farmers training, climate change perception, and weather road distance. The result from GPS estimation indicated that treatment level two the number of climate-smart practices increases household nutritional status by16%. Likewise, treatment level three and four of the number of climate-smart practices increases the household level nutritional status by 37% and 76% respectively over that of treatment level one of the climate-smart practices and is significant at a 1% statistical probability level. This study has found evidence that the adoption of climate-smart on the households’ nutrition security status. Therefore, the result of this study would be expected to significantly contribute as policy and strategic inputs for policymakers in designing rural livelihood improvement policies and to the beneficiary in enhancing their welfare and living standard.